(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1994)
Fourteen pectinid and oyster species from the Pliocene Loreto Basin (Baja California Sur, Mexico) are recorded and discussed with regard to their relationships with closely related taxa. The whole assemblage points toward a Pliocene age. Aequipecten dallasi and Argopecten abietis abietis resulted to be the most useful biostratigraphic taxa, being restricted to Pliocene. The bulk of the considered species were confined within southern regions during the Pliocene. Crassostrea californica osunai is likely to have been endemic of Baja California Sur. Pectinids and oysters appear to have inhabited fine to coarse shallow infralittoral bottoms wave- or current-nfluenced. The environmental energy was the main factor controlling presence/absence of species. Finally, a unusual vermetid-Nodipecten association is described and interpreted in terms of paleoenvironmental meaning.